Surging Capital Flows to Emerging Asia : Facts, Impacts, and Responses - Nowak, Sylwia (IMF Working Papers; Working Paper ;, 2012)
Net capital flows to emerging Asia rebounded at a record pace following the global financial crisis, raising concerns about overheating and financial stability. This paper documents the size and composition of the most recent surge to Asian emerging markets from a historical perspective and compares developments in the broader economy, asset prices, and corporate variables across the different episodes of strong inflows. We find little evidence of a significant build-up of imbalances and resource misallocation during the most recent surge. We also review country experiences in managing the risks associated with inflows and argue that Asian countries have used regulatory measures during past surges, although there is not strong evidence of their efficacy without supporting monetary and fiscal policies.